Reviewing the Palaeoenvironmental Record to Better Understand Long-Term Human-Environment Interaction in Inner Asia During the Late Holocene - Spate, Michael; Leipe, Christian; Motuzaite Matuzeviciute, Giedre (Frontiers in Ecology and Evolution, 2022)
The Middle to Late Holocene spread of agro-pastoralism throughout Eurasia not only subjected domesticated taxa to stressors associated with novel environments, but induced changes in these environments following the introduction of these social-ecological systems. The mountainous region of Inner Asia comprises various steppe, meadow and forest landscapes where zooarchaeological evidence suggests occupation by herding populations as early as 7000 years Before Present (BP). Recent archaeobotanical findings indicate introduction of cropping and the development of agro-pastoralism by 4500 BP. Here we review and synthesise palaeoenvironmental studies and data to examine anthropogenic impacts and modification of these landscapes. From around 4000 BP we find significant changes in palynomorph, charcoal, sediment and other proxy data, relating to the introduction of agriculture to the region, with later intensifications in land-use indicators at around 2000 and 1000 BP. We note that these impacts are not uniform or continuous through and across the records and may be evidence of shifting phases of occupation and landscape management. This temporal and spatial variability may also be in response to shifts in moisture availability due to Holocene long-term changes in the intensity of the summer monsoon and Westerly circulation systems. Changes among arboreal pollen indicate the development of intensified use of forest resources in the region, which we identify as an a topic for future investigation. Based on these data, we stress the long-term human palaeoecology in the study area and argue that traditional agro-pastoralist systems should be considered in future programs of landscape conservation in the region. This study also emphasises the importance for future local-scale multi-proxy studies into past anthropogenic change within the Inner Asian landscape.